Collaborative Real-World Analysis (CReW-A) with Video Analysis: Fostering Creativity and Analytical Skills in Physics Teacher Education - Firdaus, Thoha; Sinensis, Arini Rosa (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2026)
Physics teacher candidates often struggle to connect kinematics concepts with authentic motion phenomena, particularly when interpreting graphs, identifying relevant variables, and transforming observations into quantitative representations. This study evaluated the implementation of the previously developed Collaborative Real-World Analysis (CReW-A) learning model assisted by video analysis. Conducted within a Design and Development Research framework, the study employed a one-group pretest–posttest design involving physics education students. Creativity was evaluated using a validated rubric covering originality, elaboration, fluency, and resistance to premature closure, while analytical skills were measured through pretest and posttest assessments. The findings show that students produced highly creative video-analysis products and demonstrated substantial improvement in analytical skills following the intervention. Learning gains were categorized as moderate, accompanied by statistically significant improvement and a strong educational effect. These findings suggest that integrating authentic real-world observation, collaborative learning, video-based analysis, graph interpretation, and reflective discussion provides an effective pedagogical approach for fostering creativity and strengthening analytical skills in physics teacher education. The CReW-A model offers promising implementation evidence for promoting meaningful and technology-enhanced physics learning